Effort Improving Learning Outcomes Using IT-Based Media for Students Class II SD Negeri Wanutunggal Godong District, Grobogan Regency Academic Year 2020/2021 - Puspitasari, Wina (Universitas Sebelas Maret, 2020)
This research was conducted because of the low learning outcomes of class II SD Negeri Wanutunggal. The method that researchers use in this classroom action research. The subjects in this study were students of class II SD Negeri Wanutunggal which consisted of 26 students. Data were collected by researchers through observation, interviews, tests, and documentation. The results showed that: 1) The application of the CTL model can increase the activities of teachers and students. In the results of observations of teacher activity in cycle I, namely 72.52, and increased to 90.32 in cycle II. While the results of observations of student activity in the first cycle were 70.83, and increased to 91.7 in the second cycle. 2) The increase in student learning outcomes can be seen from the average score of students in Indonesian subjects in the first cycle of 72.7 with a percentage of 69.23%, in the second cycle it was 78.4, with a percentage of 80.8%. In mathematics subjects also experienced an increase, namely in the first cycle of 69.5, with a percentage of 57.7%, in the second cycle it became 77 with a percentage of 80.76%.